Kesiapan Pendidik dan Tenaga Kependidikan dalam Mengimplementasikan Kurikulum Merdeka - Maylitha, Evi; Alfiyana, Fahrid Maruf; Iskandar, Mochamad Fahmi; Nurdiansyah, Muhamad Farhan; Hanifa, Syakira; Prihantini, Prihantini (Indo-MathEdu Intellectuals Journal, 2023)
Curriculum Merdeka is a diverse intracurricular learning system, allowing students to have sufficient time to understand concepts and improve their competencies. Its implementation requires major contributions from educators and education personnel. This study aims to describe their readiness to implement Curriculum Merdeka. The research method used is quantitative descriptive. The data collection technique used is to use questionnaire deployment. The results show that overall, teachers are adequately prepared in the implementation of Curriculum Merdeka, although some still experience obstacles in compiling learning materials. This is evidenced by a yield percentage of 56%. For school principals, overall, the principal is able and ready to implement the Curriculum Merdeka. The ability to know the characteristics and participation in the Curriculum Merdeka training reached a percentage of 80%. School supervisors who have an important role show that they are capable enough in implementing the Curriculum Merdeka. One thing to note, that the ability to master curriculum material, basic framework to the preparation of teaching modules and project modules occupies a percentage of 60%.